Focusing on cancer patients' intentions to use psychooncological support: A longitudinal, mixed‐methods study. Issue 6 (30th April 2018) - Tondorf, T.; Grossert, A.; Rothschild, S.I.; Koller, M.T.; Rochlitz, C.; Kiss, A.; Schaefert, R.; Meinlschmidt, G.; Hunziker, S.; Zwahlen, D.
Abstract: Objective: Distress screening programs aim to ensure appropriate psychooncological support for cancer patients, but many eligible patients do not use these services. To improve distress management, we need to better understand patients' supportive care needs. In this paper, we report the first key finding from a longitudinal study that focused on patients' intentions to use psychooncological support and its association with distress and uptake of the psychooncology service. Methods: We conducted a prospective, observational study in an Oncology Outpatient Clinic and assessed distress, intention to use psychooncological support, and uptake of the psychooncology service by using the Distress Thermometer, a semistructured interview, and hospital records. We analyzed data with a mixed‐methods approach. Results: Of 333 patients (mean age 61 years; 55% male; 54% Distress Thermometer ≥ 5), 25% intended to use the psychooncology service (yes), 33% were ambivalent (maybe), and 42% reported no intention (no). Overall, 23% had attended the psychooncology service 4 months later. Ambivalent patients reported higher distress than patients with no intention (odds ratio = 1.18, 95% confidence interval [1.06‐1.32]) but showed significantly lower uptake behavior than patients with an intention (odds ratio = 14.04, 95% confidence interval [6.74‐29.24]). Qualitative analyses revealed that ambivalent patients (maybe) emphasized fears and uncertainties, while patients with clear intentions (yes/no) emphasized knowledge, attitudes, and coping concepts. Conclusions: We identified a vulnerable group of ambivalent patients with high distress levels and low uptake behavior. To optimize distress screening programs, we suggest addressing and discussing patients' supportive care needs in routine clinical practice.